Molecular dynamics simulations of quinine encapsulation into biodegradable nanoparticles: A possible new strategy against Sars-CoV-2. (5th September 2021) - Stipa, Pierluigi; Marano, Stefania; Galeazzi, Roberta; Minnelli, Cristina; Laudadio, Emiliano
Graphical abstract: Highlights: PLA chains tended to interact with themselves, while PGA maximized the interactions with water molecules and ions. The copolymer PLGA increased the interactions with solvent preserving a compact form, allowing a reasonable time of degradation. Quinine molecules generated strong interaction with themselves, leading to a little bioavailable agglomerate. Quinine molecules quickly diffused in the water phase due to very weak interactions with the PGA chains. Every quinine molecule rested in the polymer core surrounded by polymer chains, avoiding the formation of agglomerate increasing the quinine bioavailability. Abstract: A new coronavirus disease, SARS-CoV-2, has spread into a global pandemic in December 2019. Since no specific therapeutic drugs for treating COVID‐19 have been approved by FDA, recent studies suggest that the known antimalarial quinine and its derivatives (chloroquine and hydroxychloroquine) inhibit receptor binding of the viral particles and inhibits the strong "cytokine storm", which is the main cause of death among infected patients. In particular, the natural alkaloid quinine has shown to possess a better safety profile and greater tolerability compared to its derivatives. Dosage optimization of quinine is still necessary as the currently available dosage forms have controversial pharmacokinetics and safety profiles. Therefore, repurposing quinine dosage forms to improve its pharmacokinetics and safety profile may be necessary to support its use against SARS-CoV-2. In this context, biodegradable/biocompatible polymeric nanoparticles may provide a safe site-specific and controlled quinine delivery, reducing the frequency of drug administration and the dose. In this study, a full atomistic molecular dynamics simulation approach has been used to investigate the use of poly-(glycolic acid) and poly-(lactic acid) and their copolymer poly-(lactic-co-glycolic acid) as potential delivery systems for lipophilic quinine to get insights into the mechanism of quinine encapsulation and release at the atomic/molecular level.